Educação científica infantil em espaços não formais funcionais - Silva, Luis Carlos Soares da (2022)
Scientific education emerges during the technological changes past the last decades, aiming to inform and form people on the technologies use and their implications for society and nature. Even though scientific education is affected by the context in which it is inserted, in Brazil, it acquires a character-focused on the axes of science education over time, focusing on helping students to understand science and its influences, enabling them to make good decisions in society, whether these are personal or that culminate in representational choices. Scientific education must take place as soon as possible. Therefore, opportunities must be given to students even in early childhood education, as they already have affinities with technologies, thus contributing to the end of late scientific education. The evaluation systems of science education (PISA and Saeb) show worrying indices regarding science teaching in Brazil. The non-formal functional spaces such as forests, trails, national parks, planetariums, museums, squares, and science centers, contribute to the children's scientific education development, working like a methodological tool. This research is exploratory, descriptive, and documentary, having a qualitative approach in nature. Structured observation and a form containing specific elements for the characterization of spaces were used as a data collection instrument. As a result of the study, three places in script format were pointed out in the contribution of an approach in science education with early childhood education, since they present physical and structural conditions for these activities development. In this research, the main trail of the Parque Nacional Serra de Itabaiana (PNSI), the Parque dos Falcões, and the Praça Fausto Cardoso were analyzed as non-formal functional spaces in the Microregion of Agreste de Itabaiana. These spaces offer different resources, where teachers can develop studies, observations, and environmental education, education for heritage, ecological trails, among other activities for educational purposes.